PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN DI TOKO INTAN MARKET LINTAS MELAWI SINTANG - Sore, Avelius Dominggus; Suryati, Eka; Pelipa, Emilia Dewiwati (Jurnal Pendidikan Ekonomi (JURKAMI), 2023)
To satisfy customers by effectively meeting their demands. businesses must be able to develop benefits for the goods and services they provide. The goal of this study was to ascertain how customer happiness at Toko Intan Market Lintas Melawi Sintang was impacted by service quality. In this study. a descriptive quantitative research methodology was applied. With a sample size of 100 respondents. the population in this study consists of customers of the diamond shop located at the cross-Melawi sintang market in 2020. employing incidental sampling for sampling. A questionnaire is the method of data collecting that is utilized. Using a Likert scale. study factors are evaluated. Validity and reliability tests are used to evaluate the questionnaire instrument. Testing the correlation test. simple linear regression test. and coefficient of determination are all included in data analysis. From the research results, it can be inferred that there is a substantial correlation between customer satisfaction and service quality, depending on the criteria. The findings of the t test and significance indicate that at Toko Intan Market Lintas Melawi Sintang, there is a strong relationship between service quality and customer satisfaction. The determination test findings reveal that the independent variable contributes 37.30% to the dependent variable, with other variables accounting for the remaining 62.70%.